2018
DOI: 10.1002/celc.201800932
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on the Reversible Intercalation of Magnesium‐Ions into V2O5 Electrodes

Abstract: The choice for solvents in electrolyte solutions for non‐aqueous magnesium batteries is currently limited to ethers. However, the scientific community regularly uses acetonitrile (ACN) based electrolyte solutions as model systems in order to characterize new cathode materials for rechargeable Magnesium batteries. In this study, we demonstrated the effect of dimethoxyethane (DME), an important solvent for rechargeable magnesium systems, on the reversible intercalation of Mg2+ cations into thin, monolithic V2O5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 62 publications
1
63
0
Order By: Relevance
“…Moreover, recent research found that DME, which is a very important solvent in non-aqueous Mg electrochemistry, has a negative impact on the intercalation of Mg ions into a V 2 O 5 cathode. 53 Clearly, integration of high-voltage cathode material with a magnesium metal anode in the appropriate electrolyte solution, to form a high-energy magnesium battery, is no trivial undertaking.…”
Section: Mg Metal Anode/electrolyte/cathode Compatibilitymentioning
confidence: 99%
“…Moreover, recent research found that DME, which is a very important solvent in non-aqueous Mg electrochemistry, has a negative impact on the intercalation of Mg ions into a V 2 O 5 cathode. 53 Clearly, integration of high-voltage cathode material with a magnesium metal anode in the appropriate electrolyte solution, to form a high-energy magnesium battery, is no trivial undertaking.…”
Section: Mg Metal Anode/electrolyte/cathode Compatibilitymentioning
confidence: 99%
“…A stable open circuit voltage (OCV) of 3.42 V versus Li indicates complete oxidation of vanadium. [ 43 ] A typical cyclic voltammogram (CV) of V 2 O 5 spheres at 0.25 mV s −1 is shown in Figure S1 (Supporting Information). The CV curve shows two distinct reduction peaks at 3.34 V, and 3.14 V versus Li along with a shoulder peak at 3.08 V versus Li, indicating the reduction of V +5 into a mixture of V +4 and V +3 along with the formation of ε‐Li x V 2 O 5 and δ‐Li x V 2 O 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure a displays the first galvanostatic charge/discharge profile of V 2 O 5 spheres that exhibit specific discharge capacity of 225 mA h g −1 with distinct and flat charge and discharge plateaus demonstrating significantly improved kinetics than previous reports. [ 26,37,43,46,47 ] Further in order to understand the charge/discharge mechanism, the differential capacity (d Q /d V ) is plotted versus voltage from the galvanostatic data (Figure 3b). During intercalation, two distinct peaks are observed that are positioned at ≈2.04 V (vs Mg/Mg +2 ) and ≈2.01 V (vs Mg/Mg +2 ), while during deintercalation, three peaks appear at 2.17 V (vs Mg/Mg +2 ), 2.18 V (vs Mg/Mg +2 ), and 2.20 V (vs Mg/Mg +2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this perspective, multivalent-ion technologies (Mg 2+ , Ca 2+ , Al 3+ ) have been proposed as replacements for Li-ion technology because they can store more charge per ion at the cathode, leading to larger energy density than the univalent ion batteries [3]. Among them, magnesium-ion batteries have attracted attention due to the high abundance of magnesium (1.94 %) [4], high volume specific capacity (3833 mAh cm -3 ) [5] and low reduction voltage (-2.37 V vs. SHE) [6].…”
Section: Introductionmentioning
confidence: 99%